The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0024061
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions in Children—A Systematic Review

Abstract: BackgroundAdverse drug reactions in children are an important public health problem. We have undertaken a systematic review of observational studies in children in three settings: causing admission to hospital, occurring during hospital stay and occurring in the community. We were particularly interested in understanding how ADRs might be better detected, assessed and avoided.Methods and FindingsWe searched nineteen electronic databases using a comprehensive search strategy. In total, 102 studies were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
276
7
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(318 citation statements)
references
References 81 publications
(68 reference statements)
21
276
7
9
Order By: Relevance
“…Few studies found female preponderance while certain others, no such correlation. 1,3,6,13,14 In our study, however, there was male The commonest ADRs were local site reactions (Table 1) which is in concordance with previous studies. According to a study done in Shanghai 1 and a systematic review by Smyth et al large proportion of ADRs were local site reactions and mostly due to vaccines.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Few studies found female preponderance while certain others, no such correlation. 1,3,6,13,14 In our study, however, there was male The commonest ADRs were local site reactions (Table 1) which is in concordance with previous studies. According to a study done in Shanghai 1 and a systematic review by Smyth et al large proportion of ADRs were local site reactions and mostly due to vaccines.…”
Section: Discussionsupporting
confidence: 92%
“…According to a study done in Shanghai 1 and a systematic review by Smyth et al large proportion of ADRs were local site reactions and mostly due to vaccines. 3 Vaccine related studies by Choe et al in Korea and Aagard et al in Danish children reported the same. 19,20 Skin is the most common organ involved in hypersensitivity to drugs and biological substances.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Una revisión sistemática de 102 estudios prospec-tivos 9 de RAM en niños, encontró gran variación cuando se compararon las tasas de incidencia reportadas desde estudios observacionales; entre los estudios, 36 estimaron una tasa de incidencia para RAM durante la hospitalización desde 0,6% a 16,8% de los pacientes; considerando que una de las principales dificultades, cuando se comparan tasas de incidencia para RAM, es que los estudios difieren en la calidad metodológica, escenario clínico, características de la población y duración del estudio.…”
Section: Discussionunclassified